(-3x+5)(x-6)=0

Simple and best practice solution for (-3x+5)(x-6)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-3x+5)(x-6)=0 equation:


Simplifying
(-3x + 5)(x + -6) = 0

Reorder the terms:
(5 + -3x)(x + -6) = 0

Reorder the terms:
(5 + -3x)(-6 + x) = 0

Multiply (5 + -3x) * (-6 + x)
(5(-6 + x) + -3x * (-6 + x)) = 0
((-6 * 5 + x * 5) + -3x * (-6 + x)) = 0
((-30 + 5x) + -3x * (-6 + x)) = 0
(-30 + 5x + (-6 * -3x + x * -3x)) = 0
(-30 + 5x + (18x + -3x2)) = 0

Combine like terms: 5x + 18x = 23x
(-30 + 23x + -3x2) = 0

Solving
-30 + 23x + -3x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(-6 + x)(5 + -3x) = 0

Subproblem 1

Set the factor '(-6 + x)' equal to zero and attempt to solve: Simplifying -6 + x = 0 Solving -6 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + x = 0 + 6 x = 0 + 6 Combine like terms: 0 + 6 = 6 x = 6 Simplifying x = 6

Subproblem 2

Set the factor '(5 + -3x)' equal to zero and attempt to solve: Simplifying 5 + -3x = 0 Solving 5 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -3x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -3x = 0 + -5 -3x = 0 + -5 Combine like terms: 0 + -5 = -5 -3x = -5 Divide each side by '-3'. x = 1.666666667 Simplifying x = 1.666666667

Solution

x = {6, 1.666666667}

See similar equations:

| (p-8)2=13 | | 7(4s+7)=385 | | 17-3x=-1 | | (3x+5)(2x-12)=0 | | 6(x+1)=90 | | (5x+3)(x+6)=0 | | 4(a-1)=84 | | (x-6)(x^2-3x+4)= | | (5x+3)(x-6)=0 | | Log(2x-4)=4 | | (3x-5)(x-6)=0 | | 8x=(13x+3) | | (X*40)+(x*1.5*10)=923 | | 8x=13x+3 | | x+x-6=47 | | 4(r=20)=1/5(20r=400) | | 5x-3(2-1x)=1-2x | | 4x^2-3x+7=11 | | 2(a+b)-10= | | x=2y+3w | | 2(AB)-10= | | x^3+6x^2-36=0 | | 2(A*B)=10 | | x^3+6x^2-36=30 | | (2x+2)(5x^2+3x-2)= | | 5+x=x*2.37500 | | 10x^2+-21=0 | | 2x*x^2=6 | | e^5x-9=12 | | 6+12(10-x)=84 | | j-63/2=2 | | 3+(x-2)-3x=3(4x-2) |

Equations solver categories